‘It’s always in the back of my mind’: understanding the psychological impact of recovery following pancreaticoduodenectomy for cancer: a qualitative study - Anna Kathryn Taylor; Carolyn Anne Chew-Graham; David Chang; Lara Rimmer; Ambareen Kausar (BMJ Open)
Objectives Ten per cent of patients diagnosed with pancreatic cancer undergo pancreaticoduodenectomy. There is limited previous research focusing on psychological well-being; unmet support needs impact negatively on quality of life. This paper reports the psychological impact of a pancreatic cancer diagnosis and subsequent pancreaticoduodenectomy, exploring how patients’ lives alter following surgery and how they seek support.Design Inductive qualitative study involving in-depth semistructured interviews with 20 participants who had undergone pancreaticoduodenectomy for pancreatic or distal biliary duct cancer. Interviews were audiorecorded, transcribed and anonymised, and thematic analysis used principles of constant comparison.Setting Single National Health Service Trust in Northwest England.Participants Patients were eligible for inclusion if they had had pancreaticoduodenectomy for head of pancreas cancer, periampullary cancer or distal cholangiocarcinoma between 6 months and 6 years previously, and had completed adjuvant chemotherapy.Results Analysis identified the following main themes: diagnosis and decision making around surgery; recovery from surgery and chemotherapy; burden of monitoring and ongoing symptoms; adjusting to ‘a new normal’; understanding around prognosis; support-seeking. Participants seized the chance to have surgery, often without seeming to absorb the risks or their prognosis. They perceived that they were unable to control their life trajectory and, although they valued close monitoring, experienced anxiety around their appointments. Participants expressed uncertainty about whether they would be able to return to their former activities. There were tensions in their comments about support-seeking, but most felt that emotional support should be offered proactively.Conclusions Patients should be made aware of potential psychological sequelae, and that treatment completion may trigger the need for more support. Clinical nurse specialists (CNSs) were identified as key members of the team in proactively offering support; further training for CNSs should be encouraged. Understanding patients’ experience of living with cancer and the impact of treatment is crucial in enabling the development of improved support interventions.